2022
DOI: 10.3390/ijms232314962
|View full text |Cite
|
Sign up to set email alerts
|

TRPV3 and Itch: The Role of TRPV3 in Chronic Pruritus according to Clinical and Experimental Evidence

Abstract: Itching is a sensory phenomenon characterized by an unpleasant sensation that makes you want to scratch the skin, and chronic itching diminishes the quality of life. In recent studies, multiple transient receptor potential (TRP) channels present in keratinocytes or nerve endings have been shown to engage in the propagation of itch signals in chronic dermatological or pruritic conditions, such as atopic dermatitis (AD) and psoriasis (PS). TRPV3, a member of the TRP family, is highly expressed in the epidermal k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…TRPV3, abundantly found in epithelial cells, probably is the most essential TRPV channel to skin physiology and pathophysiology [ 26 ] and participates in various processes, including skin barrier formation [ 4 ], hair cycle regulation [ 6 ], and wound healing [ 5 ]. The level of TRPV3 mRNA and/or protein in skin cells was reported to be altered in several conditions, such as dermatitis [ 16 , 30 , 31 ], suggesting its potential role in the development of skin conditions [ 32 ]. Moreover, excessive TRPV3 activity was shown to be associated with inflammation and itches in Olmsted syndrome [ 10 , 11 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…TRPV3, abundantly found in epithelial cells, probably is the most essential TRPV channel to skin physiology and pathophysiology [ 26 ] and participates in various processes, including skin barrier formation [ 4 ], hair cycle regulation [ 6 ], and wound healing [ 5 ]. The level of TRPV3 mRNA and/or protein in skin cells was reported to be altered in several conditions, such as dermatitis [ 16 , 30 , 31 ], suggesting its potential role in the development of skin conditions [ 32 ]. Moreover, excessive TRPV3 activity was shown to be associated with inflammation and itches in Olmsted syndrome [ 10 , 11 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have documented a significant increase in TRPV3 channel expression in severe scalp psoriatic lesions characterized by intense itching [ 13 , 65 ]. Importantly, gain-of-function mutations in TRPV3, identified in both mice and humans, are characterized by severe itching, hyperkeratosis, and elevated total IgE levels [ 29 , 66 ].…”
Section: Ion Channels In Keratinocytesmentioning
confidence: 99%
“…An increasing number of studies have shown that keratinocyte-expressed TRPV3 is involved in chronic pruritus and itch transmission [76]. Han et al [77] reported that citrusinine-II, a plant-derived natural acridone alkaloid from A. monophylla, is a potent and selective antagonist of TRPV3 that has a strong antipruritic effect in both in vivo and in vitro experiments.…”
Section: Trp Cation Channel Subfamily V (Vanilloid) Member 2 (Trpv2)mentioning
confidence: 99%